Action to meet the World Food Demand - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Mahmoud El-Soul, Director General of ICARDA (International Center for Agricultural Research in the Dry Areas) classifies the main responsibility of the World Community. Video by Meerim Shakirova, Social Media Reporter